2023
DOI: 10.1038/s41597-023-02074-6
|View full text |Cite
|
Sign up to set email alerts
|

An integrated single-cell transcriptomic dataset for non-small cell lung cancer

Abstract: As single-cell RNA sequencing (scRNA-seq) has emerged as a great tool for studying cellular heterogeneity within the past decade, the number of available scRNA-seq datasets also rapidly increased. However, reuse of such data is often problematic due to a small cohort size, limited cell types, and insufficient information on cell type classification. Here, we present a large integrated scRNA-seq dataset containing 224,611 cells from human primary non-small cell lung cancer (NSCLC) tumors. Using publicly availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 74 publications
(98 reference statements)
0
9
0
Order By: Relevance
“…Because pancreatic cancer is known to be the most collagen-rich cancer, we started our investigation by analyzing collagen gene expression in a publicly available single-cell RNA-seq dataset of pancreatic ductal adenocarcinoma (PDAC) patients [26]. Here, we identified subtypes of CAFs and their collagen profile, which we confirmed in a public non-small cell lung cancer (NSCLC) dataset [27]. To investigate whether these CAF-associated collagens were associated with patient outcome in PDAC and other cancers, we profiled the collagen gene expression in tumor samples from The Cancer Genome Atlas (TCGA) project [28] and evaluated the association with survival outcomes.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Because pancreatic cancer is known to be the most collagen-rich cancer, we started our investigation by analyzing collagen gene expression in a publicly available single-cell RNA-seq dataset of pancreatic ductal adenocarcinoma (PDAC) patients [26]. Here, we identified subtypes of CAFs and their collagen profile, which we confirmed in a public non-small cell lung cancer (NSCLC) dataset [27]. To investigate whether these CAF-associated collagens were associated with patient outcome in PDAC and other cancers, we profiled the collagen gene expression in tumor samples from The Cancer Genome Atlas (TCGA) project [28] and evaluated the association with survival outcomes.…”
Section: Introductionmentioning
confidence: 82%
“…We used the 'FindAllMarkers' and 'FindMarkers' functions to test differential expression of collagens in the identified CAF subtypes. We analyzed NSCLC single-cell RNA-seq data from Prazanowska and Lim [27], which includes data from seven separate datasets comprising a total of 185 NSCLC tumor samples. This integrated dataset excluded cells with under 200 or over 3,000 genes per cell and cells with over 20% mitochondrial genes.…”
Section: Single-cell Rna-seq Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies on sex differences in the bladder were rarely reported, and the molecular mechanisms underlying these sex differences are not fully understood until now. In recent years, scRNA-seq has become a powerful tool to measure gene expression and explore cellular heterogeneity [ 24 ]. To explore the sex-based differences in bladder, we collected scRNA-seq data of six normal human bladders from public databases for further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) data used in this study were obtained from a publicly available dataset, originally published by Karolina Hanna Prazanowska and Su Bin Lim. 27 The Seurat object of the final processed scRNA-seq dataset, including uniform manifold approximation and projection (UMAP) embeddings and precomputed cell cluster assignments, was accessed and downloaded from Figshare (https://doi.org/10.6084/m9.figsh Stromal M2-like TAM density showed a high degree of variation among the 221 LUSC TMA specimens (mean ± SD, 572.9 ± 537.4), while islet M2-like TAM density was also highly variable (mean ± SD, 158.7 ± 242.9; Figure 1C,E; Table 1). Stromal M2-like TAM density was moderately correlated with islet M2-like TAM density (r = 0.408, p < 0.0001).…”
Section: Reanalysis Of Single-cell Rna Sequencing Datamentioning
confidence: 99%